Invention of space exploration - Downs, Mike (It changed the world., 2020)
Elucidates the impact of space exploration on society, discussing how exploration has enlightened our understanding of the universe, produced useful technologies, and made it possible to conceive of missions to Mars. Concludes with a glossary, text-dependant questions, an activity, and an index.